Sistem Penjadwalan Perkuliahan Multi-Level Berbasis Cloud dengan Validasi Real-time dan Notifikasi WhatsApp untuk Transparansi Beban Akademik - Dony Kusuma Hadi; Hudan Studiawan; Hadziq Fabroyir (Limits: Journal of Mathematics and Its Applications, 2026)
Traditional lecture scheduling systems are often inefficient, prone to conflicts, and lack transparency in teaching workload distribution. This study has developed a cloud-based automated timetabling system that integrates Google Workspace and WhatsApp to address the complexities of multi-level (undergraduate, master’s, and doctoral) course scheduling in higher education environments. The system combines constraint-based validation with a heuristic algorithm to enable real-time conflict detection and transparent distribution of credit-hour-based teaching loads. Implemented on a real-world dataset of 120 courses (including parallel classes), 11 classrooms, and 26 lecturers, the system successfully generated schedules less than 17 seconds. Real-time validation achieved a response time of 1.2 seconds per edit data in cell, and the automated notification module delivered teaching load summaries to 95% of lecturers via WhatsApp and email. The system improved administrative efficiency compared to manual processes and enhanced the accountability of academic resource management through real-time visibility and user-centric communication